Comparison of Intra-articular Injection of Hyaluronic Acid and N-Acetyl Cysteine in the Treatment of Knee Osteoarthritis: A Pilot Study. (October 2017) - Ozcamdalli, Mustafa; Misir, Abdulhamit; Kizkapan, Turan Bilge; Uzun, Erdal; Duygulu, Fuat; Yazici, Cevat; Kafadar, Ibrahim Halil
Objective: To compare the relative effectiveness of intra-articular N -acetyl cysteine (NAC) and hyaluronic acid (HA) on pain, function and cartilage degradation markers in patients with mild to moderate knee osteoarthritis (OA). Design: We prospectively conducted a clinical trial with 20 patients having a diagnosis of Kellgren-Lawrence grade 2-3 knee OA, and randomly allocated to the HA or NAC groups. Groups were matched on age, sex, and body mass index. Injections of 3-mL HA (Hylan G-F 20) or 3-mL NAC (Asist ampoule) were administered as a single shot. Functional status and pain were evaluated before and after injection, using the Western Ontario and McMaster Universities Arthritis Index (WOMAC) and the visual analogue scale (VAS) scores. Pre- and posttreatment concentrations of serum C-reactive protein (CRP), synovial fluid chondroitin-6-sulfate (C-6S), matrix metalloproteinase-3 (MMP-3), cross-linked C-terminal telopeptide of type 2 collagen (CTX-II), total oxidant status (TOS), and total antioxidant concentration (TAC) were obtained. Results: WOMAC, VAS scores, and CRP levels were comparable between groups prior to treatment. Both HA and NAC produced comparable reductions in TOS and MMP-3. NAC was more effective in reducing C-6S and CTX-II ( P < 0.05). No effects on TAC were noted. Conclusions: NAC is effective in lowering some cartilage degradation markers, with comparable outcomes to HA for pain and function. NAC could provide a cheaper alternative to HA for intra-articular injection treatment of mild to moderate knee OA. Future placebo controlled trials are warranted to evaluate effectiveness in a larger patient population with a wider range of age and OA severity.